The Effect Of Firm Efficiency On Firm Value Of Public Companies In Indonesia With It Investments And The Covid-19 Pandemic As Moderating Variables - Neng Nurhasanah; Bowo Setiyono (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of the establishment of the company is to maximize wealth for shareholders. The increase in shareholder and company wealth is represented by firm value. The higher the firm value, the higher the wealth of shareholders. The increase in shareholder wealth through increasing firm value is influenced by several factors, including how efficiently the company is managing its resources. The use of information technology (IT) is believed to increase firm efficiency. The rapid increase in the total confirmed cases and the COVID-19 pandemic affected not only health conditions but also gradually led to a global crisis that affected almost every country around the world. Amid increasing uncertainty during the COVID-19 pandemic, firm efficiency is needed by companies to survive. This study aims to determine the effect of firm efficiency on firm value. This research was conducted on companies listed on the IDX for the period 2017-2021. This study uses moderating variables in the form of Information Technology (IT) investment and the Covid-19 pandemic. It also uses control variables consisting of company size, financial leverage, and cash holding. The results of this study showed that IT investment has a significant negative effect on firm efficiency. The Covid-19 pandemic has had a significant negative effect on firm efficiency. Firm efficiency has a positive effect on firm value. This study also finds that IT investment weakens the relationship between firm efficiency and firm value, and the Covid-19 pandemic strengthens the relationship between firm efficiency and firm value.